2020
DOI: 10.3389/fmicb.2020.00933
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity in the Neptune Forest: Comparison of the Mycobiota of Posidonia oceanica, Flabellia petiolata, and Padina pavonica

Abstract: Fungi are widely distributed in the Oceans, interact with other organisms and play roles that range from pathogenic to mutualistic. The present work focuses on the characterization of the cultivable mycobiota associated with the seagrass Posidonia oceanica (L.) Delile collected off the Elba Island (Italy). We identified 102 taxa (mainly Ascomycota) by the mean of a polyphasic approach. Leaves, rhizomes, roots and matte were characterized by unique mycobiota revealing a "plant-part-specificity." The comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…Lulworthiaceae is the sole family in the Lulworthiales order, and Lulworthiaceae spp. are regarded as strictly marine species, which include the following genera: Cumulospora, Halazoon, Hydea, Kohlmeyerella, Lulwoana, Lulworthia, Lindra, Matsusporium, and Moleospora (Poli et al, 2020). Recently, a novel genus was introduced to the Lulworthiaceae, Paralulworthia, with two new species described, Paralulworthia gigaspora and Paralulworthia posidoniae (Poli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lulworthiaceae is the sole family in the Lulworthiales order, and Lulworthiaceae spp. are regarded as strictly marine species, which include the following genera: Cumulospora, Halazoon, Hydea, Kohlmeyerella, Lulwoana, Lulworthia, Lindra, Matsusporium, and Moleospora (Poli et al, 2020). Recently, a novel genus was introduced to the Lulworthiaceae, Paralulworthia, with two new species described, Paralulworthia gigaspora and Paralulworthia posidoniae (Poli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…are regarded as strictly marine species, which include the following genera: Cumulospora, Halazoon, Hydea, Kohlmeyerella, Lulwoana, Lulworthia, Lindra, Matsusporium, and Moleospora (Poli et al, 2020). Recently, a novel genus was introduced to the Lulworthiaceae, Paralulworthia, with two new species described, Paralulworthia gigaspora and Paralulworthia posidoniae (Poli et al, 2020). Hyde et al (2020) also included the following genera in the family: Haloguignardia, Lolwoidea, Moromyces, Orbimyces, Rostrupiella, and Sammeyersia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seagrasses are owering plants inhabiting marine environments and have a worldwide distribution, with 50 species reported that cover about 60,000 km 2 (Logan 1992;Phang 2000;Raghukumar 2017). Seagrasses provide food, habitats, and breeding grounds to a variety of marine species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, meadows of seagrass are important carbon sinks and sequester between 10 to 18% of the ocean's carbon reservoir for long-term storage (Pernice et al 2016). Seagrasses prevent erosion by trapping and binding sediments and by their death, provide substantial amounts of nutrition to organisms living within the seagrass ecosystem, as well as to those in mangroves and corals and other ecosystems (Wilson 1998;Phang 2000;Raghukumar 2017). Primary productivity of seagrass meadows is among the highest of aquatic ecosystems (Duarte and Chiscano 1999).…”
Section: Introductionmentioning
confidence: 99%